Effects of 405-nm LED Treatment on the Resistance of Listeria monocytogenes to Subsequent Environmental Stresses - Kang, Shenmin; Meng, Yujie; Cheng, Xiaomeng; Tu, Junhong; Guo, Du; Xu, Yunfeng; Liang, Sen; Xia, Xiaodong; Shi, Chao (Frontiers in Microbiology, 2019)
Listeria monocytogenes can persist under a wide range of stress conditions, contributing to its ubiquitous distribution and unique pathogenic traits. Light from light-emitting diodes (LEDs) has recently been shown to inactivate various pathogens. Thus, the aim of the present study was to evaluate the effects of light treatment using a 405-nm LED on the subsequent resistance of L. monocytogenes to environmental stresses, including oxidative stress, ultraviolet (UV) irradiation, low temperature, osmotic pressure, simulated gastric fluid (SGF), and bile salts. Following 405-nm LED illumination at 4°C for 150 min, the survival of L. monocytogenes was examined after exposure to oxidative stress (0.04% H2O2), UV irradiation (253.7 nm), low temperature (4°C), osmotic pressure (10%, 15%, or 20% NaCl), SGF (pH 2.5), or bile salts (2%). The mechanisms responsible for changes in stress tolerance were identified by assessing the transcriptional responses and membrane integrity of L. monocytogenes. The 405-nm LED treatment reduced the resistance of L. monocytogenes to all the stresses tested. Reverse transcription quantitative real-time polymerase chain reaction analysis indicated that the transcription of multiple genes associated with stress resistance, including betL, gbuA, oppA, fri, bsh, and arcA, was reduced by 405 nm LED. Confocal laser scanning microscopy revealed that 405-nm LED treatment disrupted the integrity of the L. monocytogenes cell membrane compared with untreated bacteria. Therefore, 405-nm LED illumination appears to reduce the resistance of L. monocytogenes to various stress conditions. These findings suggest that 405-nm LED treatment could be used to effectively prevent and/or control with L. monocytogenes contamination along the entire food-processing chain, from production to consumption.